Citric Acid in Dairy Products Alters Liver and Kidney in Mice - Majid, Walaa Najah; Albyati, Sheereehan Abdullhussein; Naji, Wafaa Abdulmutalib (Procedia of Engineering and Life Science, 2025)
General Background: Food preservatives like citric acid are widely used in dairy products to inhibit microbial growth and extend shelf life. Specific Background: Although generally recognized as safe, concerns have arisen regarding potential adverse health effects with long-term or high-dose consumption. Knowledge Gap: Limited research exists on the histopathological and biochemical effects of citric acid as a preservative in mammalian models. Aims: This study aimed to assess the impact of oral administration of citric acid (3%) on liver and kidney tissues, as well as on biochemical markers in male white mice. Results: Histological analyses revealed notable degenerative changes in liver and kidney tissues, including glomerular shrinkage, inflammatory infiltration, hepatocyte vacuolization, and sinusoidal hemorrhage. Biochemically, treated mice exhibited significant elevations in ALT, AST, serum creatinine, and urea levels compared to controls (p < 0.05). Novelty: This study provides integrated evidence from both histological and biochemical parameters demonstrating the potential toxicity of citric acid when used excessively. Implications: Findings suggest the need for reevaluation of citric acid’s safety profile at common exposure levels and encourage further toxicological studies to inform food safety standards.Highlight : The study reveals that 3% citric acid causes significant histological damage to both liver and kidney tissues in male mice. Biochemical analysis showed elevated levels of ALT, AST, creatinine, and urea in the treated group. Results highlight potential health risks associated with prolonged intake of citric acid as a food preservative. Keywords : Citric Acid, Dairy Products, Kidney, Liver, Preservatives